Empirical estimate of fundamental frequencies and damping for Italian buildings. - Gallipoli, Maria Rosaria (Earthquake engineering & structural dynamics.)
The aim of this work is to estimate the fundamental translational frequencies and relative damping of a large number of existing buildings, performing ambient vibration measurements. The first part of the work is devoted to the comparison of the results obtained with microtremor measurements with those obtained from earthquake recordings using four different techniques: horizontal-to-vertical spectral ratio, standard spectral ratio, non-parametric damping analysis (NonPaDAn) and half bandwidth method. We recorded local earthquakes on a five floors reinforced concrete building with a pair of accelerometers located on the ground and on top floor, and then collected microtremors at the same location of the accelerometers. The agreement between the results obtained with microtremors and earthquakes has encouraged extending ambient noise measurements to a large number of buildings. We analysed the data with the above-mentioned methods to obtain the two main translational frequencies in orthogonal directions and their relative damping for 80 buildings in the urban areas of Potenza and Senigallia (Italy). The frequencies determined with different techniques are in good agreement. We do not have the same satisfactory results for the estimates of damping: the NonPaDAn provides estimates that are less dispersed and grouped around values that appear to be more realistic. Finally, we have compared the measured frequencies with other experimental results and theoretical models. Our results confirm, as reported by previous authors, that the theoretical period?height relationships overestimate the experimental data.